Promotional Asymmetry in Retail: Why Special Offers Matter More Than Conventional Discounts: Asimetri Promosi dalam Ritel: Mengapa Penawaran Khusus Lebih Penting daripada Diskon Konvensional - Riomas Sinurat; Edward Alezandro Lbn. Raja; Netty Niawati Gea (Khazanah Multidisiplin, 2026)
This study examines the influence of Discount Programs and Special Offers on consumer Purchasing Decisions at Matahari Department Store, Thamrin Plaza Medan. The research is important because promotional strategies are widely used in retail, yet different promotional formats may generate unequal consumer responses. A quantitative explanatory design with a cross-sectional survey approach was employed. Primary data were collected through questionnaires administered to 70 consumers selected from a population of 230 customers using incidental sampling. The data were analyzed using multiple linear regression, partial t-tests, simultaneous F-tests, and the adjusted coefficient of determination with SPSS version 16. The findings show that Discount Programs have a positive but statistically insignificant effect on Purchasing Decisions, with a regression coefficient of 0.242, a t-value of 1.698, and a significance value of 0.094. In contrast, Special Offers have a positive, significant, and dominant effect, with a coefficient of 0.686, a t-value of 5.869, and a significance value of 0.000. Simultaneously, both variables significantly affect Purchasing Decisions and explain 44.9% of their variation. These findings imply that retailers should prioritize relevant, transparent, and value-added Special Offers while using conventional discounts selectively. The originality of this study lies in revealing the differential and complementary effects of two promotional mechanisms within an offline department-store context, showing that consumers respond more strongly to additional value, urgency, and exclusivity than to price reductions alone.